2017
DOI: 10.2174/0929866524666170214125847
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Amyloid-like Fibril Formation of Trypsin by Red Wines

Abstract: Abstract:The aim of the present study was to examine the potential role and applicability of dietary supplements in reducing the risk of development of amyloid diseases associated with the gastrointestinal tract, such as type II diabetes. Trypsin, a well-known serine protease was used as a model protein in our experiments. The effect of various red wines on the formation of amyloid-like fibrils of trypsin was studied in vitro, in aqueous ethanol, at pH 7.0. Turbidity measurements, aggregation kinetics experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Although the sensitivity of the turbidity method is low, it can be a good tool when larger aggregates are formed [21,26]. Fuentes et al also showed results in which peppermint proved to be a good islet amyloid polypeptide amyloid inhibitor [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the sensitivity of the turbidity method is low, it can be a good tool when larger aggregates are formed [21,26]. Fuentes et al also showed results in which peppermint proved to be a good islet amyloid polypeptide amyloid inhibitor [9].…”
Section: Discussionmentioning
confidence: 99%
“…CR is a well-known amyloid specific dye, which upon binding with the amyloid exhibits increase in absorption with a characteristic red shift [2]. CR specifically binds against β-pleated sheet conformation, and does not bind to the proteins with shorter β-pleated structures [21]. If the fibrils are present in the sample, and CR dye is added, the absorption maximum is displaced from 490 nm to 510 nm.…”
Section: Discussionmentioning
confidence: 99%
“…The total phenolic content of the grapefruit seed extract was determined, and it was 495.5 mg GAE/l. Compared to other inhibitory agents the efficiency of inhibition of amyloid formation did not change proportionally with the total phenolic content in the presence of the grapefruit seed extract [24]. It is probable that polyphenolic compounds are not the only responsible factors for the fibril formation inhibitory effect, but also other compounds are involved.…”
mentioning
confidence: 84%
“…32,33 An increase in the absorption at 350 nm indicates a greater degree of aggregation. 34 The sample without fruit juice showed maximum absorption whereas in the presence of different juices it was significantly reduced. All the juices we used inhibited aggregation, but their levels of effectiveness were different.…”
mentioning
confidence: 92%